International justice against war criminals - BONDARENKO Наталія; SYTNICHENKO Олена (Ius Modernum, 2024)
The main prerequisites for the emergence and functioning of international criminal tribunals, Ukraineʼs cooperation with the International Criminal Court and its institutions are highlighted. The purpose of the article is to substantiate the proposal regarding the need to create a special international tribunal to investigate and prosecute war criminals for aggression against Ukraine, taking into account the current norms of national and international law. The methods used are: dialectical, historical, systemic analysis and synthesis, formal-logical, hermeneutic. Russian aggression against Ukraine created the largest conflict in Europe since the Second World War, causing many war crimes, genocide, crimes against humanity. The world community should react to this in a similar way to the holding of international criminal tribunals in Nuremberg, Tokyo, Yugoslavia and Rwanda, which created international precedents for the conviction of war criminals and helped to overcome the personal immunity of the highest state and military officials guilty of crimes of aggression. Consideration of the legal aspects of Ukraine’s interaction with the International Criminal Court proved the need for our state to ratify the Rome Statute for full participation in the Courtʼs proceedings. It was emphasized that the establishment of general peace and justice regarding the punishment of war criminals depends both on Ukraine and on the active actions of the West and the European Parliament.